The Evaluation of the Effect of Neuropathic Pain on Functional Disability in Patients with Chronic Low Back Pain - Yalkın Çalık; Ayça Filiz Çalık (Galenos Yayinevi, 2015)
Objective: The aim of this study was to evaluate both the prevalence of neuropathic pain (NP) and the effect of functional disability of NP in patients with chronic low back pain (CLBP). Materials and Methods: In this study, outpatients data were reviewed retrospectively from January 2014 to December 2014 to determine the patients with CLBP. 190 patients with CLBP meeting the inclusion criteria were included. NP scores of the patients were assessed using Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) and the evaluation of pain was performed using the Visual analoque scale (VAS) and functional disability scores was determined by the Oswestry disability index (ODI). Results: In this study NP was detected in 39.4% of the patients with CLBP. The number of female patients with NP (n=60, %80) was significantly higher than the number of male patients with NP (n=15, %20), (p<0.05). ODI and VAS scores of the patients with NP [(19.81±7.28), (5.08±0.76)] was significantly higher than those of the patients without NP [(15.28±6.83), (4.44±1.14)], (p<0,001). Conclusion: It was found that the co-existence of NP with CLBP increases pain and functional disability.